A randomized, double‐blind, single‐dose study to assess bioequivalence of MB02 biosimilar after manufacturing iteration and reference bevacizumab - C. Schwabe; A. Cole; A. Espigares‐Correa; M. E. Beydon; A. Florez‐Igual; J. Queiruga‐Parada (Wiley, 2023)
Abstract To investigate and compare the pharmacokinetic (PK) profiles of MB02 products, before and after optimizing the manufacturing process, and reference bevacizumab to establish bioequivalence between them. In this randomized, double‐blind, single dose, parallel study, 114 healthy male volunteers were randomized 1:1:1 to receive a 1 mg/kg intravenous dose of MB02‐SP, MB02‐DM, or US‐bevacizumab. The follow‐up period was 100 days. PK similarity between them was determined using the standard bioequivalence criteria (0.80-1.25) for the area under the serum concentration-time curve from time 0 extrapolated to infinity and the maximum observed serum concentration. Study results showed that the PK profiles of bevacizumab were similar. Statistical analysis demonstrated that for each pairwise comparison there were no differences. The 90% CIs for the ratios of geometric least squares means were fully contained within the predefined similarity acceptance limits and ranged from 0.899 to 1.12 for area under the curve and from 0.887 to 1.11 for maximum concentration. A total of 159 adverse events were reported by 76 subjects who received the study drug. The majority (90.6%) of the reported adverse events were grade 1 in severity, with 9.4% as grade 2 in severity. None were considered as grade 3, 4, or 5. Treatment‐induced anti‐drug antibodies incidence was 21.6%, 33.3%, and 23.7% for the treatment of MB02‐SP, MB02‐DM, and US‐bevacizumab, respectively. No subjects showed treatment‐induced neutralizing anti‐drug antibodies. This study demonstrates the PK, safety, and immunogenicity similarity and bioequivalence of MB02‐SP, MB02‐DM, and the reference product bevacizumab.